Performance evaluation of the MAGLUMI Hepatitis B virus surface antigen chemiluminescence immunoassay - Shen, Lihong; Zhang, Yun; Shi, Min; Shao, Lijia; Feng, Shengchun; Li, Weiting; Fang, Zhonggang; Yin, Jun; Li, Tinghua (Journal of medical virology, 2024)
A highly sensitive and reliable Hepatitis B virus surface antigen (HBsAg) measurement is essential to universal screening, timely diagnosis, and management of Hepatitis B virus (HBV) infection. This study aimed to evaluate the performance of MAGLUMI HBsAg chemiluminescence immunoassay (CLIA). MAGLUMI HBsAg (CLIA) was compared against ARCHITECT HBsAg. 411 HBsAg positive samples, including different stages of infection, genotypes, subtypes, mutants, and 30 seroconversion panels were tested to evaluate diagnostic sensitivity. Diagnostic specificity was evaluated by testing 205 hospitalized samples and 5101 blood donor samples. Precision, limit of blank (LoB), limit of detection (LoD), and linearity were also verified. The diagnostic sensitivity of the MAGLUMI HBsAg (CLIA) was 100% with better seroconversion sensitivity than ARCHITECT HBsAg. The MAGLUMI HBsAg (CLIA) has optimal detection efficacy for HBV subgenotypes samples. The analytical sensitivity is 0.039 IU/mL. The initial diagnostic specificity is 99.63% on blood donors and 96.59% on hospitalized samples. The verification data demonstrated high repeatability, a LoB of 0.02 IU/mL, LoD of 0.05 IU/mL and an excellent linearity of 0.050–250 IU/mL (R2 = 0.9946). The MAGLUMI HBsAg (CLIA) is proved a highly sensitive and reliable assay with optimal subgenotype detection efficacy.